What Is It Like to Be a Player? The Qualia Revolution in Game Studies. (September 2017) - Mosca, Ivan
The article aims to explore the reasons why the discipline of game studies requires a shift toward player analysis. This can be done without leaving an object-oriented approach, thanks to the efforts of social ontology, a recent philosophical discipline that investigates social facts. The integration of social ontology into the research on games will be displayed through some mind experiments on the nature of the paradigmatic example of rules. The result of this integration leads to give up the reductionism shared by the majority of game scholars.